2016
DOI: 10.1590/1982-43272663201611
|View full text |Cite
|
Sign up to set email alerts
|

School Bonding of Adolescent Offenders

Abstract: Students strongly bonded to the educational institution are more motivated to study and less likely to present behavioral problems and/or juvenile delinquency. This study's objective was to verify the existence of variations in school bonding among different groups of adolescents and identify the most problematic aspects among adolescents in conflict with the law from the perspective of Marc LeBlanc's Social and Personal Control Theory of Deviant Behavior. The 60 adolescents participating in the study responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
6
0
9
Order By: Relevance
“…Referring specifically to 'investment,' from the School Control model perspective, as well as, in the literature, school investment is stimulated by performance, as already pointed out (LeBlanc, 2003;Silva et al, 2016). In the present study, the best investment results were found in the groups of adolescent students (O-S and NO-S), with no differences between them, but significantly different from the O-Drop group.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Referring specifically to 'investment,' from the School Control model perspective, as well as, in the literature, school investment is stimulated by performance, as already pointed out (LeBlanc, 2003;Silva et al, 2016). In the present study, the best investment results were found in the groups of adolescent students (O-S and NO-S), with no differences between them, but significantly different from the O-Drop group.…”
Section: Discussionsupporting
confidence: 77%
“…At school, they invest a good part of their daily time, interacting with teachers and colleagues and participating in activities, which promotes cognitive, and social and emotional development (Calejon, 2017;Silva & Bazon, 2014). Adolescent offenders seem to have a predominantly negative school experience, which is reflected in poor performance and high dropout rate (Calejon, 2017;Cunha & Dazzani, 2016;Silva, Cianflone, & Bazon, 2016). In 2011, in Brazil, 57% of adolescent offenders deprived of liberty evicted from school at the time of apprehension, and 8% were not literate (National Council of Justice, CNJ, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para outros adolescentes, contudo, a participação no bullying certamente se constitui em fator de risco ao desenvolvimento saudável, de forma geral, e à delinquência, de forma específica. No tocante à delinquência especificamente, é possível que o impacto do bullying seja mediado pela fragilização do vínculo escolar e, provavelmente, pela naturalização da violência que tal experiência gera (Silva, Cianflone, & Bazon, 2016). Esse tipo de reflexão merece que pesquisas mais apuradas sejam realizadas, mas já oferece pistas para o delineamento mais consistente de estratégias de intervenção e de prevenção da intimidação entre pares no ambiente escolar.…”
Section: Considerações Finaisunclassified
“…No domínio escolar, três escalas do QCJ distinguiram os grupos no T1: Escola Desorganizada/Deteriorada, Problemas de Comportamento e Bom Desempenho Acadêmico, nas quais o GV pontuou mais alto em todas. Os adolescentes do GV perceberiam suas escolas como mais desorganizadas, em termos de indisciplina, de prática de delitos em seu interior e de degradação física, reiterando uma imagem que, no geral, representa uma visão bastante negativa do ambiente escolar, algo muito comum em meio a adolescentes infratores, e que muitas vezes antecede a evasão da escola (Silva, Cianflone & Bazon, 2016). Os adolescentes do GV também indicaram ter, mais frequentemente, histórico de problema de comportamento em contexto escolar, assinalados por meio de sanções como suspensões e expulsões, o que também contribuiria para compor o conjunto de experiências negativas/estressantes em contexto escolar.…”
Section: Londresunclassified